A Manual of Methods and Procedures for the Regional Waterway Management System - Robert A. Swett; David A. Fann (EDIS)
TP-124, a 91-page illustrated manual by Robert Swett and David Fann, details the procedures that are necessary to complete a Regional Waterway Management System for Florida’s coastal canals and other waterways. Includes references. Published by the Florida Sea Grant College Program, December 2001. Reviewed March 2008.